2012
DOI: 10.2298/jsc111013006p
|View full text |Cite
|
Sign up to set email alerts
|

Poly(urethane-siloxane)s based on hyperbranched polyester as crosslinking agent: Synthesis and characterization

Abstract: A series of novel polyurethane crosslinked structures (PUs) was prepared from α,ω-dihydroxy-(ethylene oxide-poly(dimethylsiloxane)-ethylene oxide) (EO-PDMS-EO), 4,4’-methylenediphenyl diisocyanate and Boltorn® hyperbranched polyester of the third pseudo generation. The hydroxyfunctional hyperbranched aliphatic polyester with 26 end groups was used as crosslinking agent. In order to improve the compatibility of all reactants during the synthesis, PU samples were prepared by a step-growth polymerization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
2
13
0
3
Order By: Relevance
“…The large number of terminal hydroxyl groups present in Boltorn ® HBPs enables fast formation of networks that have good mechanical properties, as well as good resistance to chemicals [11][12][13][14], while the presence of PDMS contributes to the good thermal and surface properties, and to elasticity of the highly crosslinked materials. In our previous studies, we have investigated the influence of the content of !,"-dihydroxyethoxy propyl-poly(dimethylsiloxane) (EO-PDMS) and type of HBPs on the swelling behavior, morphological, thermal and thermomechanical properties of PU networks [15][16][17][18][19][20][21]. These results confirmed that physical and thermal properties are related to the crosslinking density, hydrogen bonding interactions, microphase separation and content of EO-PDMS soft segment.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…The large number of terminal hydroxyl groups present in Boltorn ® HBPs enables fast formation of networks that have good mechanical properties, as well as good resistance to chemicals [11][12][13][14], while the presence of PDMS contributes to the good thermal and surface properties, and to elasticity of the highly crosslinked materials. In our previous studies, we have investigated the influence of the content of !,"-dihydroxyethoxy propyl-poly(dimethylsiloxane) (EO-PDMS) and type of HBPs on the swelling behavior, morphological, thermal and thermomechanical properties of PU networks [15][16][17][18][19][20][21]. These results confirmed that physical and thermal properties are related to the crosslinking density, hydrogen bonding interactions, microphase separation and content of EO-PDMS soft segment.…”
supporting
confidence: 55%
“…Catalyst concentration was kept at 0.02 wt% [25][26][27]. The details for the synthesis of similar PU networks are given in our previously published papers [16][17][18][19][20][21]. Compositions of the synthesized PUs and weights of the reactants used for the synthesis of PUs are presented in Table 1.…”
Section: Synthesis Of Pu Films Based On Pdmsmentioning
confidence: 99%
“…Polyurethane networks based on PDMS macrodiols and Boltorn® HBPs appear to be promising candidates for different applications, especially in coatings, since such multicomponent system can link and combine various properties of all its constituents [18][19][20]. Large number of end hydroxyl groups in HBP is responsible for the fast curing and creation of the highly crosslinked system with good chemical resistance and mechanical properties, while PDMS provides good thermal and surface properties and elasticity in such highly crosslinked material, because of its low glass transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Noting that, even there exist long carbon chains in the structure, LCPSi also exhibits relatively higher thermostability than the reported ones. For instance, the Y c of a poly(urethane‐siloxane) based on hyperbranched polyester is lower than 5 wt% at 700°C, while the Y c of a hyperbranched poly(siloxysilane) synthesized is lower than 5 wt% at about 600°C; therefore, LCPSi prepared herein shows certain advantages in terms of the thermal performance among hyperbranched polysiloxanes.…”
Section: Resultsmentioning
confidence: 91%